Potential role of polycyclic aromatic hydrocarbons as mediators of cardiovascular effects from combustion particles - Jørn A. Holme; Bendik C. Brinchmann; Magne Refsnes; Marit Låg; Johan Øvrevik (BMC, 2019)
Abstract Air pollution is the most important environmental risk factor for disease and premature death, and exposure to combustion particles from vehicles is a major contributor. Human epidemiological studies combined with experimental studies strongly suggest that exposure to combustion particles may enhance the risk of cardiovascular disease (CVD), including atherosclerosis, hypertension, thrombosis and myocardial infarction. In this review we hypothesize that adhered organic chemicals like polycyclic aromatic hydrocarbons (PAHs), contribute to development or exacerbation of CVD from combustion particles exposure. We summarize present knowledge from existing human epidemiological and clinical studies as well as experimental studies in animals and relevant in vitro studies. The available evidence suggests that organic compounds attached to these particles are significant triggers of CVD. Furthermore, their effects seem to be mediated at least in part by the aryl hydrocarbon receptor (AhR). The mechanisms include AhR-induced changes in gene expression as well as formation of reactive oxygen species (ROS) and/or reactive electrophilic metabolites. This is in accordance with a role of PAHs, as they seem to be the major chemical group on combustion particles, which bind AhR and/or is metabolically activated by CYP-enzymes. In some experimental models however, it seems as PAHs may induce an inflammatory atherosclerotic plaque phenotype irrespective of DNA- and/or AhR-ligand binding properties. Thus, various components and several signalling mechanisms/pathways are likely involved in CVD induced by combustion particles. We still need to expand our knowledge about the role of PAHs in CVD and in particular the relative importance of the different PAH species. This warrants further studies as enhanced knowledge on this issue may amend risk assessment of CVD caused by combustion particles and selection of efficient measures to reduce the health effects of particular matters (PM).